Self-supporting soft carbon fibers as binder-free and flexible anodes for high-performance sodium-ion batteries. (15th October 2018) - Gao, Xueping; An, Yongling; Zhang, Wenshu; Yu, Menglan; Ci, Lijie; Feng, Jinkui
ABSTRACT: Sodium batteries are considered as the most promising candidates for next generation power source. Carbon materials are the most viable anode material for sodium ion batteries. However, graphic soft carbons, the most widely used anodes in lithium ion batteries due to its higher electronic conductivity and density, are fail to work in sodium ion batteries due to the larger Na + radius. Here, in our reports, soft carbon fibers derived from industrialized wet spun polyacrylonitrile (PAN) precursor are fabricated under different heat treatment temperature. When characterized as binder and conductive agent free anode for sodium ion batteries, the soft carbon fibers (1250°C) deliver an initial reversible capacity 190 mAh g −1 and a good capacity retention of 93% even after 100 cycles. The excellent electrochemical performance makes the soft carbon fibers promising choices as anodes for sodium ion batteries.